6. KERJA SAMA INDONESIA DAN CINA DALAM MENANGGULANGI PERDAGANGAN KAYU ILEGAL - Puspitasari, Luthfia; Windiani, Reni; Farabi, Nadia (Journal of International Relations, 2016)
This research aims to determine the cause of increasing illegal timber trade from Indonesiato China within 2010-2015. During that time, both countries established bilateralcooperation through Memorandum of Understanding Between the Ministry of Forestry ofthe Republic of Indonesia and the State Forestry Administration of the People’s ofRepublic of China Concerning the Cooperation in the Field of Forestry which was signedon September 15th, 2010. This is a qualitative research, using explanation. This researchused neorealist theory. As the consequences this research showed that the cause ofgrowing in illegal timber trade from Indonesia to China is weak supervision in borderregions and law enforcement against criminal acts of forestry in Indonesia. Besides, Chinais not seriously implement the MoU. This situation occurs because China got relative gainsless than Indonesia.